Critical Analysis of HIPC Initiative Contributions to Poverty Alleviation in Cameroon's Social Sector - Mbu Arrey Enow-Mangeb, John (The Graduate School, Ajou University, 2010)
ABSTRACT The word “Poverty” is not new in our society. Poverty has long existed and today, it is more or less a normal situation and part of everyday life in many societies around the world. The challenges and problems caused by poverty abound. It remains one of the major global issues that need to be tackled. The UN estimates that more than 1.4 billion people around the world live in extreme poverty, most of whom have neither shelter nor food. The UNICEF estimates that about 25,000 children die every day of poverty and related issues. Most of the poor live in remote villages and communities and cannot afford, or lack access to, good health, clean water and nutrition. Many die of hunger and starvation. The UN as well as many other international agencies, NGOs and states have been active trying to help resolve issues of poverty around the world. Many aid and assistance programs have been adopted to help the Least Developed Countries tackle issues of poverty and related problems that affect their societies. Poverty remains an issue in Cameroon, like most Sub-Saharan countries. Despite efforts put in place to free the people from poverty, most communities, especially in remote villages and rural areas, are subjected to abject poverty situations. There is the need for government to reach out to most remote communities and villages with development initiatives in order to alleviate poverty and improve living conditions. The HIPC initiative brought about joy and relief to some communities in Cameroon. Thanks to the initiative, some major projects were carried out to boost economic activities and development in the country. In the social sector, the Health and Education sub-sectors achieved quite much thanks to the initiative. The government committed itself with major reforms and strategies that could help revitalized the sector and reduce poverty.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2010. 8